ASTREINTES: THE PANORAMA OF CHANGES DEVELOPED BEFORE THE REFORM OF THE CIVIL PROCESS CODE 2015 - Menin Junior, Romeu Felix (2020)
The theme of this article is: Astreintes, the panorama of changes developed prior to the reform of the civil procedure code of 2015. The following problem was investigated: Due to the change of the CIvil code from 1973 to 2015 and expressly its interpretations, as it has been originating the proper fixation of astreintes? The following hypothesis was considered: What has been the criterion adopted by the legislator for the establishment of Astreintes. The general objective is to discuss the real change brought about by the new code in the face of the uneasiness linked to the Astreintes. The specific objectives are: To understand the characteristics; the legal nature; The historic; the origins and the fundamental role of astreintes in the civil enforcement process over time. This work is important for the society and the operator of the Law, because it addresses the reflexes resulting from an institute that is little talked about academically today and is legally relevant. This is a qualitative theoretical research lasting five months. As a result of the research carried out, it is concluded that there is, therefore, no definition in the arbitration of the astreintes, because an inadequate fixation can easily hurt the principles of proportionality and reasonableness, it is not a question of funds that originally integrate the party's credit, but legal instrument of coercion used to support executive jurisdictional provision.